Cultures Merging : A Historical and Economic Critique of Culture - Jones, E. L. (Eric Lionel) (Book collections on Project MUSE., 2006)
"Economists agree about many things--contrary to popular opinion--but the majority agree about culture only in the sense that they no longer give it much thought." So begins the first chapter of Cultures Merging, in which Eric Jones--one of the world's leading economic historians--takes an eloquent, pointed, and personal look at the question of whether culture determines economics or is instead determined by it. Bringing immense learning and originality to the issue of cultural change over the long-term course of global economic history, Jones questions cultural explanations of much social behavior in Europe, East Asia, the United States, Australia, and the Middle East. He also examines contemporary globalization, arguing that while centuries of economic competition have resulted in the merging of cultures into fewer and larger units, these changes have led to exciting new syntheses. --From publisher's description.